Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Mary Louise Frampton, Hom. Mario Olmos, Gerald Tahajian, Geri Tahajian, Irma Franson, Hon. Donald Franson, Sr. Judy Harris, Hon. Thomas Harris, Dennis Caeton